Regenerative Medicine in Brazilian Television News: Storytelling and Public Engagement - ACERO, LILIANA (Advances in Social Sciences Research Journal, 2022)
Public access to media contributes to public understandings of science and medicine. This paper explores patterns in television coverage on Brazilian regenerative medicine, as they are presented in You Tube videos that reproduce some of the main recent scientific and medical news in TV national or regional programmes regularly broadcast at peak times. The study builds upon the coproduction approach to civic epistemologies in an emerging economy – i.e. the way the wider public makes sense of public policies and demands proof of their validity, as well as, verification of their implementation. The coproduction approach is discussed in relation to two main of its analytical concepts: the public understanding of science and public engagement in science. Using textual analysis, the article chooses selected narratives on scientific sense-making processes according to the representations of reporters, scientists, as well as, patients and their families. Among other, similarities are found between global and local reporting of scientific and medical news in the videos studied: news segments validate benefits while downplaying uncertainties and legal, ethical and social concerns. Sense-making in TV news coverage is based on what can be defined as reductionist imaginaries of science and medicine. Also, news contents transmit a top-down communication model that influences the shaping of public understandings